Inactivated Piscine orthoreovirus vaccine protects against heart and skeletal muscle inflammation in Atlantic salmon. Issue 9 (21st June 2018) - Wessel, Øystein; Haugland, Øyvind; Rode, Marit; Fredriksen, Børge N.; Dahle, Maria K.; Rimstad, Espen
Abstract: Heart‐ and skeletal muscle inflammation (HSMI) caused by infection with Piscine orthoreovirus (PRV) is one of the most common viral diseases in farmed Atlantic salmon ( Salmo salar ) in Norway, and disease outbreaks have been reported in most countries with large‐scale Atlantic salmon aquaculture. Currently there is no vaccine available for protection against HSMI, partly due to the lack of a cell line for efficient virus propagation. Erythrocytes are the primary target cells for PRV in vivo and a potential source for isolation of PRV particles. In this study, PRV was purified from infected erythrocytes, inactivated and used in a vaccination trial against HSMI. A single immunization with adjuvanted, inactivated PRV induced protection against HSMI in Atlantic salmon infected by virus injection 6 weeks later, while a moderate protection was obtained in fish infected through natural transmission, i.e. cohabitation. The PRV vaccine significantly reduced PRV loads and histopathological lesions typical for HSMI compared to the unvaccinated control group. This is the first demonstration of protective vaccination against PRV, and promising for future control of HSMI in Atlantic salmon aquaculture.